Fruit Fly Pest Control with Ultrasonic Waves and Modified Steiner Trap in Orange Orchard in Narigunung 1 Village, Karo Regency - Siti Utari Rahayu; Susilawati; Suharman; Herty Afrina Sianturi; Yosatria Juanka Sibarani; Fathurrahman Fathurrahman; Jacky Gunawan Manurung; Ardiansyah Sembiring (Talenta Publisher, 2021)
Orange is one of the local fruits, which is a source of income for farmers in Narigunung 1 Village, Tiganderket District, Karo Regency. However, in recent years, many orange orchards have been attacked by the fruit fly pest of Bactrocera sp. (Diptera: Tephritidae), causing the oranges become rotten and fall. This resulted in losses for farmers; there are crop failures in some orchards, while the farmers had to pay off a large pesticide purchase. One of the effective ways to ward off the arrival of these fruit flies is by using ultrasonic waves. Based on a research, fruit flies will be disturbed if there are ultrasonic waves with a frequency of 25-30 KHz that work based on ambient temperatures above 18â°C. In addition, to control the fruit fly population, this community service also used a modified steiner trap, employing methyl eugenol, which can stimulate male fruit flies to enter the trap. Both repellents and traps will be made at a height of where fruit flies are active around the orange tree. With this control system, the orange orchard will be free from fruit flies so that farmers will no longer experience losses; besides, ecological trapping of fruit flies will reduce the population of fruit flies around Narigunung 1 Village, Karo Regency.